Nonadiabatic Photodynamics of Amantadine and 1‐Cyanoadamantane Cations - Roy, Bonasree; Titov, Evgenii; Saalfrank, Peter (Chemphyschem, 2024)
Cations of diamondoids and derivatives thereof have recently become the subject of experimental, spectroscopic studies due to their potential role in astrochemistry. In particular, their electronic spectra and photoinduced dynamics trigger great interest. Here, we report on computational investigations of two nitrogen‐containing derivatives of the adamantane cation (Ada+, C10H16+ ${{\rm{C}}_{10} {\rm{H}}_{16}^+ }$ ), the amantadine cation (Ama+, C10H15NH2+ ${{\rm{C}}_{10} {\rm{H}}_{15} {\rm{NH}}_2^+ }$ ) and the 1‐cyanoadamantane cation (Ada‐CN+, C10H15CN+). Specifically, we study electronic (vibrationally resolved) spectra and nonadiabatic molecular dynamics (modeled using the surface hopping approach based on semiempirical electronic structure theory) of these radical cations. The internal conversion time constants as well as reactive relaxation outcomes (cage‐opening and hydrogen loss) are compared for the two derivatives and also with the case of Ada+.[29] Remarkably, we find a longer ground‐state recovery time for Ada‐CN+ than for Ama+ (for the same excitation energy window), despite a smaller excitation energy for the former. Thus, a static energy gap law cannot be used to rationalize nonadiabatic dynamics and excited state lifetimes in this case: Dynamics and details of the couplings between several states play a decisive role. Nonadiabatic molecular dynamics simulations (trajectory surface hopping at the semiempirical configuration interaction singles and doubles level) predict faster internal conversion in the amantadine cation than in the cyanoadamantane cation despite a larger initial energy gap for the former. Also, electronic absorption spectra and nonadiabatic relaxation of the two derivatives are compared with those for the parent adamantane cation to understand the influence of electron donating and withdrawing groups.